If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 = 7 + x + 2 + x Reorder the terms: 29 = 7 + 2 + x + x Combine like terms: 7 + 2 = 9 29 = 9 + x + x Combine like terms: x + x = 2x 29 = 9 + 2x Solving 29 = 9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 29 + -2x = 9 + 2x + -2x Combine like terms: 2x + -2x = 0 29 + -2x = 9 + 0 29 + -2x = 9 Add '-29' to each side of the equation. 29 + -29 + -2x = 9 + -29 Combine like terms: 29 + -29 = 0 0 + -2x = 9 + -29 -2x = 9 + -29 Combine like terms: 9 + -29 = -20 -2x = -20 Divide each side by '-2'. x = 10 Simplifying x = 10
| 2x+1+3x+5+6x-31=180 | | (3xy+2yx)3= | | 12-3x=66x | | x/80=35/100 | | X+(X-5)=16 | | 5y-4=3y-18 | | 70=x+4 | | 3x^4-16x^2-81=0 | | g(x)=3f(x+1)-1 | | 28=4n+4-8 | | 4(5x-1)-(x+5)=24 | | 7x+145.5=6 | | f(x)=16x^4+8x^2+1 | | tan(19pi/12 | | 0=-2t(8t-75) | | -28=4n+4-8 | | 11x+1=5x+61 | | f(-4)=x^2-3x+9 | | 29=7+x+2 | | 2l+28=58 | | 5(n-4)=25 | | 6y=5(y+9) | | -5=y | | -8x+4(1+5x)=-6x-1 | | 8-6x+3x=-8x-3x | | 8n^2/3 | | 3/20=24/x | | 8a-6=66 | | -4x=20/3 | | 4(x+9)=2x-1 | | -8x+4(1+5x)=-6-1 | | .19x+.33=2.04 |